IMPLEMENTASI NILAI-NILAI ISRA' MI'RAJ DALAM KEGIATAN LOMBA MAHASISWA KKM DI MASYARAKAT DESA KALIREJO - Adinda Avrilie Wiwik (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2025)
Isra' Mi'raj is an important event in Islam that contains spiritual and moral values. To commemorate Isra' Mi'raj 1445 H, KKM group 50 UIN Malang students conducted activities in Kalirejo Village as a form of community service. This activity includes competitions for adhan, iqomah, colouring, memorising short surahs, and quiz, aiming to improve children's religious understanding and character. This activity involved students as committees and judges and receiving support from the community. The results showed an increase in religious understanding and interaction between students and the community, as well as a positive impact on community empowerment.